The Effect of Performance on Organizational Culture, Digital Transformation and Employee Productivity in the Company - Deny Marfriady Deny (Dinasti Publisher, 2023)
Literature study scientific articles discuss the effect of performance on organizational culture, digital transformation, and productivity in the context of human resource management science. The focus of this article is to build a hypothesis regarding the relationship between variables that will be used in future research. The research object involves online libraries, Mendeley, Google Scholar, and various other online academic media. The method used in this research is library research which involves sources of information in the form of e-books and electronic journals which can be accessed openly. The results of this article reveal that: Organizational culture has a significant and positive influence on employee performance. Digital Transformation has a significant and positive influence on employee performance. Productivity has a significant and positive influence on employee performance.